Cytokine profile in chronic hepatitis C: An observation. (August 2017) - Baskic, Dejan; Vukovic, Vuk R.; Popovic, Suzana; Djurdjevic, Predrag; Zaric, Milan; Nikolic, Ivana; Zelen, Ivanka; Mitrovic, Marina; Avramovic, Dusko; Mijailovic, Zeljko
Highlights: Cytokine levels in patients group were heterogeneous, spread in wide range of values. Grouping data according to disease-relevant factors showed high intragroup diversity. There was no correlation between cytokine levels and each disease-relevant factor. Inconsistency of literature data is a result of individual differences of patients. Abstract: The data addressing cytokine profile in chronically infected HCV patients are conflicting, ranging from Th1 or Th2 cytokine prevalence to the expression of both types of cytokines. Therefore, the aim of this study was to evaluate cytokine profile in these patients. Cytokine sera levels in HCV patients and healthy controls were evaluated using 13plex FlowCytomix Multiplex. Median values of both proinflammatory and anti-inflammatory cytokines were lower in HCV patients then in controls. In addition, the number of subjects producing detectable quantities of cytokines was significantly lower in the group of HCV patients. Yet, cytokine levels in those patients were remarkably heterogeneous ranging from low to extremely high, much higher than the maximal values in control group. Similarly, grouping data according to HCV genotype, HCV RNA load, ALT/AST ratio and the stage of fibrosis showed marked standard deviations, reflecting high intragroup diversity. No correlation was found between each disease-related factor and cytokine levels. Patients investigated in our and similar studies were disparate pursuant to characteristics of the hosts, pathogen and course of the disease. Therefore, the inconsistency of the literature data regarding cytokine pattern in chronic HCV patients may be a consequence of the disregarded/overlooked heterogeneity of these patients.